(untitled) (Third Sector Social Economic Review, 2012)
In this study, competetive concept in public sector which is continuously criticised and being thougt that to be reformed according to efficient and effective private sector, that is in nowadays agenda is analysed. Public sector aimed to compete with private sector so that to be efficient and in this way it was reformed by itself. Most important factor caused this process was new right thought. In this study, new right thought’s basic thesis; Thatcherizm, Reaganizm, deregulation, privatization and new public service evaluated basicly.